Detection of rotavirus and intestinal parasites in children under 5 years old, from indigenous communities in Zulia state, Venezuela - Aténcio Ricardo; Irama Perozo; Zulbey Rivero; Angela Bracho; Rafael Villalobos; Sergio Osorio; Maria Atencio (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2016)
Rotavirus is a viral agent associated with childhood gastroenteritis, being with intestinal parasites, the principal cause of diarrhea in children. In order to detect rotavirus, and intestinal parasites in children from 0 to 5 years old of six indigenous communities in Zulia state, 173 stool samples was recolected, where the presence of rotavirus was determinate using agglutination test. The samples were characterized macroscopically and microscopically by examining with SSF, lugol and concentrate formalin-ether to detect parasitic evolutionary forms. It was determined that the presence of intestinal parasites was 71%, significantly higher than the 16,2% of rotavirus. The most prevalent parasites were Ascaris lumbricoides (32,4%) and Blastocystis spp. (31,2%). Statistically significant relationship between the presence of rotavirus and diarrhea existence (p = 0.0001); more no presence of rotavirus among vaccinated children (p = 0.904 ). About they predominated protozoosis over helminths; as well as polyparasitism (52%). Major parasites associated with rotavirus were Blastocystis spp. and Entamoeba coli, although without statistical significance. It is concluded that the prevalence of rotavirus detected corresponds to that reported in Venezuela for children under 5 years of urban areas.